Opportunities for cross border entrepreneurship education in ASEAN region - Ab. Latif, Abdul Aziz (ASEAN Universities Consortium of Entrepreneurship Education (AUCEE), 2010)
An ASEAN region which consist ten nations has large number of population requires higher level of education. Since this region is an important economic global player, it has become important factor towards economic growth and development. Based on the current scenario in this region, several opportunities exist with regards to entrepreneurship higher education. This is supported by availability of infrastructure such as accessibility of high speed of telecommunication, accessibility of fast and low cost transport such as AirAsia, roads transport highways, financial infrastructures, and research opportunities such as in agro based industries, and other form of innovation. On the other hand, some ASEAN countries also possess shared culture and languages. In addition, the leadership in each country through the agencies supports many activities with regard to the economic development. Therefore cross border entrepreneurship development become very important in achieving economic and social development goals. Many exchange program and research among student and academician in higher education, public funded research intuitions, as well as the private sectors in ASEAN countries can be utilized.